Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/phar.1666
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus‐Induced Cardiomyopathy in an Adult Renal Transplant Recipient

Abstract: Tacrolimus-induced cardiomyopathy (TICM) is a rare but serious adverse effect of tacrolimus, which has been described primarily in pediatric non-renal transplant recipients. We describe a case of TICM in an adult renal transplant recipient that resulted in allograft dysfunction and multiple hospital admissions for heart failure exacerbation. Prompt and complete reversal of TICM occurred after tacrolimus discontinuation. Although tacrolimus-induced cardiomyopathy is reversible, availability of alternative immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…We found 18 articles, consisting of case reports and observational studies, which described hypertrophic cardiomyopathy as an adverse effect to tacrolimus therapy, occurring in a wide age range (Table 1). Although similar cases have been described in patients between the ages of 58 and 62 years, 6,8,12 with hypertrophic cardiomyopathy, 13 and another case described a premature newborn with hypertrophic cardiomyopathy whose mother had received tacrolimus during pregnancy. 14 There were no differences between men and women in the occurrence of tacrolimus-induced cardiomyopathy.…”
Section: Epidemiologymentioning
confidence: 61%
See 2 more Smart Citations
“…We found 18 articles, consisting of case reports and observational studies, which described hypertrophic cardiomyopathy as an adverse effect to tacrolimus therapy, occurring in a wide age range (Table 1). Although similar cases have been described in patients between the ages of 58 and 62 years, 6,8,12 with hypertrophic cardiomyopathy, 13 and another case described a premature newborn with hypertrophic cardiomyopathy whose mother had received tacrolimus during pregnancy. 14 There were no differences between men and women in the occurrence of tacrolimus-induced cardiomyopathy.…”
Section: Epidemiologymentioning
confidence: 61%
“… 5 However, it has also been reported in adult renal, hepatic, cardiac, and small bowel transplant recipients. 6 , 7 , 8 , 9 Hypertrophic cardiomyopathy due to tacrolimus therapy has been catalogued as non‐familial acquired cardiomyopathy by the European Society of Cardiology (ESC), 10 while the American Heart Association classifies it as secondary cardiomyopathy. 11…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in this case, RV‐FAC and RV global longitudinal strain were reduced in the setting of volume overload. Tacrolimus is known to lead a cardiomyopathy with reduced left ventricular (LV) ejection fraction and LV hypertrophy . Reduction in the RV function and strain could reflect similar myocardial impairment of the RV.…”
Section: Discussionmentioning
confidence: 99%
“…Potential direct toxic effect of CNIs on myocardium is not well studied. Previous reports have predominantly described concentric and hypertrophic cardiomyopathy following solid organ transplant [2,3]. Mc Leod et al reported a case of dilated cardiomyopathy following liver transplant which did not recover following Tacrolimus withdrawal [4].…”
Section: Introductionmentioning
confidence: 99%